The Effectiveness of Integrating Problem-Based Learning and Speed Reading Strategies in Improving Reading Speed among Medical Record Students at Sapta Bakti Bengkulu - Khodijah; Arono Sulsain Al Qowi; Wisma Yunita; Suci Dwina Darma (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2026)
The increasing complexity and volume of medical record documentation demand students to read efficiently and accurately. However, conventional learning approaches often do not adequately support the development of effective reading strategies aligned with professional needs. This study aimed to examine the effectiveness of integrating speed reading strategies within the Problem-Based Learning (PBL) model to improve reading speed among medical record students. This study employed a quasi-experimental design involving 60 second-year medical record students at STIKES Sapta Bakti Bengkulu. The intervention was conducted over six weeks by embedding speed reading techniques into the stages of the PBL learning process. Students’ reading performance was assessed using pre-test and post-test measurements of reading speed. The data were analyzed using comparative statistical analysis to determine the effectiveness of the intervention. The results showed a significant improvement in students’ reading speed after the implementation of PBL-based speed reading activities. The average reading speed increased from 150 words per minute (wpm) in the pre-test to 250 wpm in the post-test, with the difference being statistically significant (p < 0.05). These findings indicate that the integration of speed reading strategies within a problem-based learning environment effectively enhances students’ ability to process medical record texts more efficiently. In conclusion, integrating speed reading strategies into the Problem-Based Learning model is effective in improving reading speed among medical record students. This approach provides a relevant instructional strategy that supports the cognitive demands of medical record analysis and contributes to the development of effective learning practices in medical record education.